Engineered bacteria to accelerate wound healing: an adaptive, randomised, double-blind, placebo-controlled, first-in-human phase 1 trialResearch in context - Emelie Öhnstedt; Evelina Vågesjö; Andreas Fasth; Hava Lofton Tomenius; Pia Dahg; Sofia Jönsson; Nisha Tyagi; Mikael Åström; Zhanar Myktybekova; Lovisa Ringstad; Margareth Jorvid; Peter Frank; et al. (EClinicalMedicine, 2023)
Summary: Background: Impaired wound healing is a growing medical problem and very few approved drugs with documented clinical efficacy are available. CXCL12-expressing lactic acid bacteria, Limosilactobacillus reuteri (ILP100-Topical), has been demonstrated to accelerate wound healing in controlled preclinical models. In this first-in-human study, the primary objective was to determine safety and tolerability of the drug candidate ILP100-Topical, while secondary objectives included assessments of clinical and biologic effects on wound healing by traditionally accepted methods and explorative and traceable assessments. Methods: SITU-SAFE is an adaptive, randomised, double-blind, placebo-controlled, first-in-human phase 1 trial (EudraCT 2019-000680-24) consisting of a single (SAD) and a multiple ascending dose (MAD) part of three dose cohorts each. The study was performed at the Phase 1 Unit, Uppsala University Hospital, Uppsala, Sweden. Data in this article were collected between Sep 20th, 2019 and Oct 20th 2021. In total 240 wounds were induced on the upper arms in 36 healthy volunteers. SAD: 12 participants, 4 wounds (2/arm), MAD: 24 participants, 8 wounds (4/arm). Wounds in each participant were randomised to treatment with placebo/saline or ILP100-Topical. Findings: In all individuals and doses, ILP100-Topical was safe and well-tolerated with no systemic exposure. A combined cohort analysis showed a significantly larger proportion of healed wounds (p = 0.020) on Day 32 by multi-dosing of ILP100-Topical when compared to saline/placebo (76% (73/96) and 59% (57/96) healed wounds, respectively). In addition, time to first registered healing was shortened by 6 days on average, and by 10 days at highest dose. ILP100-Topical increased the density of CXCL12+ cells in the wounds and local wound blood perfusion. Interpretation: The favourable safety profile and observed effects on wound healing support continued clinical development of ILP100-Topical for the treatment of complicated wounds in patients. Funding: Ilya Pharma AB (Sponsor), H2020 SME Instrument Phase II (#804438), Knut and Alice Wallenberg foundation.